18 ALUMINUM EXPOSURE FROM PARENTERAL NUTRITION IN HOSPITALIZED INFANTS. Issue 1 (1st January 2007) - Majidi, S.; Bhatt, A.; Ybarra, R.; Krebs, N. F.
Abstract : Prolonged aluminum (Al) exposure can result in serious liver, bone, and neurologic diseases, including encephalopathy and osteomalacia. Parenteral nutrition (PN) mixtures are a source of exposure, and premature and hospitalized infants may be at particular risk for toxicity from such exposure. The Food and Drug Administration (FDA) has recommended that attempts be made to minimize Al exposure, and recommended 5 μg/kg/day as an upper safe limit. Objective and Method: Because of their high risk for Al toxicity, the objective of this study was to examine the Al exposure of 126 premature and newborn infants treated with PN. The compounding pharmacy at our hospital provided deidentified data of Al content of PN ordered for these patients over a 6-month period in 2005. Results: The mean (± SD) number of days of PN use in patients was 12.4 ± 12 days (median = 7 days). Overall mean Al from ordered PN was 356 ± 295 μg/kg/day (median 304 μg/kg/day). Thirty-eight percent of infants were on PN for > 10 days; mean exposure for this group was 398 ± 215 μg/kg/day; mean exposure for infants receiving PN for ≤ 10 days was 330 ± 332 μg/kg/day. Conclusion: Infants on PN are routinely exposed to Al levels far beyond the goal set by the FDA. The consequences of such exposure are unknown, and these data suggest that more studies are warranted on possible associated adverse physiologic outcomes. Additionally, more aggressive efforts are needed to reduce the levels of Al in PN solutions.